Extracellular vesicles and cancer stemness in hepatocellular carcinoma – is there a link? - Tian, Lu; Lu, Jingyi; Ng, Irene Oi-Lin (Frontiers in Immunology, 2024)
Hepatocellular carcinoma (HCC) is a highly aggressive malignancy, with high recurrence rates and notorious resistance to conventional chemotherapy. Cancer stemness refers to the stem-cell-like phenotype of cancer cells and has been recognized to play important roles in different aspects of hepatocarcinogenesis. Small extracellular vesicles (sEVs) are small membranous particles secreted by cells that can transfer bioactive molecules, such as nucleic acids, proteins, lipids, and metabolites, to neighboring or distant cells. Recent studies have highlighted the role of sEVs in modulating different aspects of the cancer stemness properties of HCC. Furthermore, sEVs derived from diverse cellular sources, such as cancer cells, stromal cells, and immune cells, contribute to the maintenance of the cancer stemness phenotype in HCC. Through cargo transfer, specific signaling pathways are activated within the recipient cells, thus promoting the stemness properties. Additionally, sEVs can govern the secretion of growth factors from non-cancer cells to further maintain their stemness features. Clinically, plasma sEVs may hold promise as potential biomarkers for HCC diagnosis and treatment prediction. Understanding the underlying mechanisms by which sEVs promote cancer stemness in HCC is crucial, as targeting sEV-mediated communication may offer novel strategies in treatment and improve patient outcome.